THE IMPACT OF PERSONALITY ON EMPLOYEE WELL-BEING - Najib Ahmad Marzuki (European Scientific Journal, ESJ, 2013)
Research on employee well-being has predominantly focused on health and individuals’ work lives. Complementing past research on employee well-being, the impact of personality on overall well-being was examined. The objectives of the study were to determine the relationship between personality domains (neuroticism, extraversion, openness to experience, agreeableness and conscientiousness) and well-being. It was also aimed at determining significant personality domains that contribute towards well-being of lecturers. A total of 117 lecturers from a public university in Malaysia were chosen as participants. The NEO-FFI Personality Inventory by Costa and McCrae (1992) was utilized to measure five personality domains while The 5F Wellness by Myers and Sweeney (2005) was employed to measure well-being. Results indicated that all personality domains correlated significantly with well-being. Openness to experience and conscientiousness were found to contribute significantly to well-being of lecturers followed by extraversion. The impact of these findings signifies that personality plays an important role in determining individual well-being.